2020
DOI: 10.3389/fnut.2020.599119
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Profiling of Volatile Compounds in Popular South Indian Traditional and Modern Rice Varieties by Gas Chromatography–Mass Spectrometry Analysis

Abstract: Rice (Oryza sativa L.) is one of the major cereal crops cultivated across the world, particularly in Southeast Asia with 95% of global production. The present study was aimed to evaluate the total phenolic content (TPC) and to profile all the volatile organic compounds (VOCs) of eight popular traditional and two modern rice varieties cultivated in South India. Thirty-one VOCs were estimated by gas chromatography–mass spectrometry (GC-MS). The identified volatile compounds in the 10 rice varieties belong to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 56 publications
3
22
1
Order By: Relevance
“…The aldehydes were the main volatile components of the white teff in the n-hexane extract followed by furans, terpene and esters and lower amount of hydrocarbons and pyrrole class of compounds. Ashokkumar et al [25] have identified 31 volatile compounds in the popular South Indian traditional and modern rice varieties among which were squalene and methyl stearate with relative content of 2.5-6.2% and 0.6-1.8%, respectively, and is comparable with the present study. As can be seen in Table 4, the relative contents of main volatile compounds determined in the brown teff sample were 18.4%, 16.0%, 12.5% and 9.73%, for the furfural and 5-methyl-2-furancarboxaldehyde, 2-[(methylthio)methyl]furan, benzeneacetaldehyde, respectively.…”
Section: Tentative Identification and Quantification Of Volatile Compounds Of Teff Grainsupporting
confidence: 90%
See 1 more Smart Citation
“…The aldehydes were the main volatile components of the white teff in the n-hexane extract followed by furans, terpene and esters and lower amount of hydrocarbons and pyrrole class of compounds. Ashokkumar et al [25] have identified 31 volatile compounds in the popular South Indian traditional and modern rice varieties among which were squalene and methyl stearate with relative content of 2.5-6.2% and 0.6-1.8%, respectively, and is comparable with the present study. As can be seen in Table 4, the relative contents of main volatile compounds determined in the brown teff sample were 18.4%, 16.0%, 12.5% and 9.73%, for the furfural and 5-methyl-2-furancarboxaldehyde, 2-[(methylthio)methyl]furan, benzeneacetaldehyde, respectively.…”
Section: Tentative Identification and Quantification Of Volatile Compounds Of Teff Grainsupporting
confidence: 90%
“…[19] The volatile profiles of most widely consumed cereals have been studied. [1,[20][21][22][23][24][25][26] However, to the best of the researchers' knowledge, no information is available regarding volatile compounds of teff grain [Eragrostis tef (Zuccagni) Trotter] varieties. Hence, the objectives of this study were (i) to optimize the appropriate hydro-distillation time of the white and brown teff grain samples using Clevenger apparatus, (ii) to identify and quantify the volatile compounds present in the white and brown teff grain samples using GC-MS method, and (iii) to investigate the extraction efficiency of dichloromethane and n-hexane solvents toward the volatile compounds present in the white and brown teff grain samples.…”
Section: Introductionmentioning
confidence: 99%
“…Squalene is consisted of about 13% human sebum and plays an important role in quenching singlet oxygen in UV-associated skin damage ( 9 ). Squalene has multiple applications in the cosmetics, pharmaceutical, nutraceutical, and food industries owing to its unique physiological and functional properties ( 9 , 28 , 29 ). There was great commercial demand for squalene and the global squalene production volume was 2,500 tons annually, with a value of 93 million dollars in 2013, and is expected to reach 241.9 million dollars by 2022 ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the assays, compounds present in the most active fraction were identified by Gas Chromatography - Mass Spectrometry (GC-MS) (Shimadzu QP 2010-SE, Japan) by comparing their retention indices (RIs) and the obtained mass spectra with those of the authentic standards from the NIST library. 35 Ultrapure helium was used as the carrier gas at 1 mL/min in a column (A BPX5: 30 m long; 0.25 mm internal diameter; and 0.25 µm film thickness). The GC program was: 50 ˚C (1 min); 5 ˚C/min to 250 ˚C (9 min) with a total run-time of 50 min.…”
Section: Methodsmentioning
confidence: 99%